HUBUNGAN PENGGUNAAN ALAT PELINDUNG DIRI DENGAN PENYAKIT TINEA PEDIS PADA PETANI SAYUR DAN BUAH DI DESA LAMPAH - Erika, Era Erik; Has, Dwi Faqihatus Syarifah (STIKes Mitra Keluarga, 2023)
Introduction : Tinea pedis is a fungal infection of the feet, especially between the toes and soles. 65% of vegetable and fruit farmers in Lampah Village suffer from tinea pedis. The purpose of this study was to analyze the relationship between the use of personal protective equipment and tinea pedis among vegetable and fruit farmers in Lampah Village. Method : The method used in this study is a quantitative study with a cross-sectional approach. The population of this study were vegetable and fruit farmers in Lampah Village, with a sample of 45 vegetable and fruit farmers taken through probability sampling techniques with simple random sampling. Data collection uses questionnaires and observation sheets and is analyzed using the contingency coefficient test. Result: The results of this study showed that almost all vegetable and fruit farmers in Lampah Village did not use personal protective equipment (86.7%), and most of the vegetable and fruit farmers in Lampah Village tested positive for tinea pedis (57.8%). Based on the results of the contingency coefficient test, it shows a significant value of 0.002<0.05, which shows a significant correlation. Conclusion: There is a relationship between the use of personal protective equipment and tinea pedis among vegetable and fruit farmers in Lampah Village. It is expected that more attention will be paid to personal hygiene, or the personal hygiene of farmers, and how to use and maintain personal protective equipment to prevent tinea pedis.